BaseLearn Media Pembelajaran Basis Data Berbasis Website dengan Metode Agile - Soraya, Dila; Azizul Risma, Novilda Putri; Sari, Oki Novia; Favorika, Viviana Nova (Kayon Media, 2023)
Abstract:The development of BaseLearn is motivated by the complexity of concepts in databases which is a major challenge in understanding the material and is an innovative step that aims to improve database learning through a digital platform. BaseLearn was developed using the Agile method including the stages of planning, implementation, software testing, documentation, deployment, and maintenance. The results of validation by material experts and media experts, BaseLearn received an excellent assessment with a feasibility percentage of 95%. The results of the usability test by prospective users using the UEQ method received an excellent rating. Thus, BaseLearn can make a positive contribution and make it easier to learn databases by providing a fun and not boring learning experience.Abstrak:Pengembangan BaseLearn dilatarbelakangi oleh kompleksitas konsep dalam basis data yang menjadi tantangan utama dalam pemahaman materi dan merupakan langkah inovatif yang bertujuan untuk meningkatkan pembelajaran basis data melalui platform digital. BaseLearn dikembangkan dengan metode Agile meliputi tahapan perencanaan, implementasi, tes perangkat lunak, dokumentasi, deployment, dan pemeliharaan. Hasil validasi oleh ahli materi dan ahli media, BaseLearn mendapatkan penilaian yang sangat baik dengan persentase kelayakan sebesar 95%. Hasil uji usabilitas oleh calon pengguna menggunakan metode UEQ mengdapatkan penilaian yang. Dengan demikian, BaseLearn dapat memberikan kontribusi positif dan memudahkan dalam mempelajari basis data dengan memberikan pengalaman belajar yang menyenangkan dan tidak membosankan